2013
DOI: 10.1111/tmi.12205
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clustering of soil‐transmitted helminth infections in a tribal area in southern India

Abstract: Objectives To estimate the prevalence, spatial patterns and clustering in the distribution of soil-transmitted helminth (STH) infections, and factors associated with hookworm infections in a tribal population in Tamil Nadu, India. Methods Cross-sectional study with one-stage cluster sampling of 22 clusters. Demographic and risk factor data and stool samples for microscopic ova/cysts examination were collected from 1237 participants. Geographical information systems mapping assessed spatial patterns of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 24 publications
9
53
0
5
Order By: Relevance
“…Additional school-based surveys in multiple States have been carried out in SAC in Madhya Pradesh (14.76%, Ascaris 9.84%, hookworm 4.92%), Rajasthan (21.10%, Ascaris 20.20%, hookworm 1.00%, Trichuris 0.20%) and Chhattisgarh (74.60%, Ascaris 70.40%, hookworm 10.50%, Trichuris (0.05%)252627. In the south, studies showed a higher prevalence for hookworm both in SAC (6.30%) and when all age groups were surveyed (38.00%) than Ascaris (1.50 and 1.20%)2028. Taken together, there are sufficient data to demonstrate that the current STH prevalence is high and both control of morbidity and strategies to potentially interrupt transmission are of high public health significance in India.…”
Section: Prevalence Of Soil-transmitted Helminths and Burden Of Diseamentioning
confidence: 97%
“…Additional school-based surveys in multiple States have been carried out in SAC in Madhya Pradesh (14.76%, Ascaris 9.84%, hookworm 4.92%), Rajasthan (21.10%, Ascaris 20.20%, hookworm 1.00%, Trichuris 0.20%) and Chhattisgarh (74.60%, Ascaris 70.40%, hookworm 10.50%, Trichuris (0.05%)252627. In the south, studies showed a higher prevalence for hookworm both in SAC (6.30%) and when all age groups were surveyed (38.00%) than Ascaris (1.50 and 1.20%)2028. Taken together, there are sufficient data to demonstrate that the current STH prevalence is high and both control of morbidity and strategies to potentially interrupt transmission are of high public health significance in India.…”
Section: Prevalence Of Soil-transmitted Helminths and Burden Of Diseamentioning
confidence: 97%
“…However, this goal has yet to be achieved. Common reasons for not meeting the target goal are poor healthcare infrastructure, lack of manpower, absence of essential medicines, and a deficiency of political will (Kaliappan et al, 2013 …”
Section: Global Distribution and Prevalence Of Sths In Childrenmentioning
confidence: 99%
“…For example, infection with roundworm is greater than with hookworm and whipworm. India did not meet the WHO target of 75% coverage of preventive treatment for preschool-and school-aged children by the year 2010-only 38% was achieved (Kaliappan et al, 2013).…”
Section: Soil-transmitted Helminthiasis In India-defining the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Abera & Nibret, 2014) are ignored. It has been demonstrated that the spatial distribution of different types of STH infections is very heterogeneous in neighbouring countries of Rwanda (Pullan, Kabatereine, Quinnell, & Brooker, 2010) and in other endemic areas in tropical and sub-tropical conditions (Kaliappan et al, 2013). Also, Clements, Deville, Ndayishimiye, Brooker, and Fenwick (2010) revealed different spatial patterns for different STH types in the East African Great Lakes region, with ubiquitous hookworm infection, and highly focal prevalence patterns of Ascaris lumbricoides and Trichuris trichiura.…”
Section: Introductionmentioning
confidence: 99%